Colorectal Cancer Liver Metastasis: Evolving Paradigms and Future DirectionsSummary - Luai R. Zarour; Sudarshan Anand; Kevin G. Billingsley; William H. Bisson; Andrea Cercek; Michael F. Clarke; Lisa M. Coussens; Charles E. Gast; Cristina B. Geltzeiler; Lissi Hansen; Katherine A. Kelley; Charles D. Lopez; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2017)
In patients with colorectal cancer (CRC) that metastasizes to the liver, there are several key goals for improving outcomes including early detection, effective prognostic indicators of treatment response, and accurate identification of patients at high risk for recurrence. Although new therapeutic regimens developed over the past decade have increased survival, there is substantial room for improvement in selecting targeted treatment regimens for the patients who will derive the most benefit. Recently, there have been exciting developments in identifying high-risk patient cohorts, refinements in the understanding of systemic vs localized drug delivery to metastatic niches, liquid biomarker development, and dramatic advances in tumor immune therapy, all of which promise new and innovative approaches to tackling the problem of detecting and treating the metastatic spread of CRC to the liver. Our multidisciplinary group held a state-of-the-science symposium this past year to review advances in this rapidly evolving field. Herein, we present a discussion around the issues facing treatment of patients with CRC liver metastases, including the relationship of discrete gene signatures with prognosis. We also discuss the latest advances to maximize regional and systemic therapies aimed at decreasing intrahepatic recurrence, review recent insights into the tumor microenvironment, and summarize advances in noninvasive multimodal biomarkers for early detection of primary and recurrent disease. As we continue to advance clinically and technologically in the field of colorectal tumor biology, our goal should be continued refinement of predictive and prognostic studies to decrease recurrence after curative resection and minimize treatment toxicity to patients through a tailored multidisciplinary approach to cancer care. Keywords: Colorectal Cancer Liver Metastasis, Biomarkers, Hepatic Arterial Infusion, High-Risk Colorectal Cancer, Recurrence